A retrospective audit on the introduction of post placental copper-T 380A intra uterine contraceptive device insertion at Tygerberg hospital - Bryan-Mc Innes, Michelle (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.